The migration pattern of a cementless hydroxyapatite-coated titanium stem under immediate full weight-bearing: a randomized controlled trial using model-based RSA - Reiner, Tobias; Sonntag, Robert; Kretzer, Jan Philippe; Clarius, Michael; Jakubowitz, Eike; Weiss, Stefan; Ewerbeck, Volker; Merle, Christian; Moradi, Babak; Kinkel, Stefan; Gotterbarm, Tobias; Hagmann, Sébastien (Journal of Clinical Medicine, 2020)
(1) Background: High primary stability is important for the long-term survival of cementless femoral stems in total hip arthroplasty (THA). The objective of this study was to investigate the migration pattern of a hydroxyapatite-coated cementless hip stem developed for minimally invasive surgery using model-based radiostereometric analysis (RSA). (2) Methods: In this randomized controlled trial, 44 patients with an indication for cementless primary THA were randomly allocated to receive either the SL-PLUS MIA stem, developed for minimally invasive surgery, or the SL-PLUS stem (Smith & Nephew Orthopaedics, Baar, Switzerland) which served as a control group. Unlimited weight-bearing was permitted postoperatively in both groups. Model-based RSA was performed after six weeks and after 3, 6, 12 and 24 months postoperatively. (3) Results: Mean total stem subsidence at two-year follow-up was 0.40 mm (SD 0.66 mm) in the SL-PLUS group and 1.08 mm (SD 0.93 mm) in the SL-PLUS MIA group (p = 0.030). Stem subsidence occurred during the first six weeks after surgery, indicating initial settling of the stem under full weight-bearing. Both stem designs showed good osseointegration and high secondary stability with no further migration after initial settling. (4) Conclusions: Settling of a cementless straight femoral stem occurs during the first six weeks after surgery under full weight-bearing. Although initial stem migration was higher in the SL-PLUS MIA group, it had no influence on secondary stability. All implants showed good osseointegration and high secondary stability with no signs of implant loosening during this two-year follow-up period.